2020
DOI: 10.3390/socsci9070120
|View full text |Cite
|
Sign up to set email alerts
|

The Culture of Violent Talk: An Interpretive Approach

Abstract: One of the defining characteristics of extremist movements is the adherence to an ideology highly antagonistic to the status quo and one that permits or explicitly promotes the use of violence to achieve stated goals and to address grievances. For members of extremist groups, talk is one of the most concrete manifestations of how adherents communicate their ideas to each other and the general public. These discussions, however, do not necessarily involve a direct correspondence between words and future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…9 Speaking violently is often key to this process of building and policing an extremist collective identity. 10 By speaking violently online, participants show their commitment to the cause, set and police boundaries and identify political and social enemies and prescribe courses of action. 11 Using violent language can also act as a stand in for taking actual violent action, releasing and demonstrating extremist fervour without having to put yourself at risk.…”
Section: Violent Online Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Speaking violently is often key to this process of building and policing an extremist collective identity. 10 By speaking violently online, participants show their commitment to the cause, set and police boundaries and identify political and social enemies and prescribe courses of action. 11 Using violent language can also act as a stand in for taking actual violent action, releasing and demonstrating extremist fervour without having to put yourself at risk.…”
Section: Violent Online Communitiesmentioning
confidence: 99%
“…10 By speaking violently online, participants show their commitment to the cause, set and police boundaries and identify political and social enemies and prescribe courses of action. 11 Using violent language can also act as a stand in for taking actual violent action, releasing and demonstrating extremist fervour without having to put yourself at risk. 12 Yet for a small number of individuals, violent rhetoric is insufficient and some choose to put this dialogue into action.…”
Section: Violent Online Communitiesmentioning
confidence: 99%
“…CRIS research on far-right communities and messaging on Facebook, Twitter and Gab has found high direct calls for violence as well as high levels of what Simi and Windisch (2020) refer to as 'violent talk': 'messaging that cultivates, normalizes and reinforce hatred, dehumanization and aggressive hostility toward minority groups and the "political enemy"' . According to Simi and Windisch (2020: 2), 'the effects of violent talk are indeterminate'.…”
Section: Political Violence and Hate Crimesmentioning
confidence: 99%
“…CRIS research on far-right communities and messaging on Facebook, Twitter and Gab has found high direct calls for violence as well as high levels of what Simi and Windisch (2020) refer to as 'violent talk': 'messaging that cultivates, normalizes and reinforce hatred, dehumanization and aggressive hostility toward minority groups and the "political enemy"' . According to Simi and Windisch (2020: 2), 'the effects of violent talk are indeterminate'. They argue that, on the one hand, it may be a verbal substitute for violent behaviour, but, on the other hand, Violent talk helps enculturate individuals through socialization processes by communicating values and norms.…”
Section: Political Violence and Hate Crimesmentioning
confidence: 99%
“…Pete Simi and Steven Windisch (Simi and Windisch 2020) analyze extreme right discourses in the United States in their study in this issue, "The Culture of Violent Talk." As their analysis is empirically grounded in rich ethnographic data collected from interviews with white supremacists in the United States since 1997, it provides us with invaluable insight into the ideology behind the rise of Trumpism and its apogee at the Capitol in January 2021.…”
mentioning
confidence: 99%